The influence of Tellurium an Folic Acid Adminitration on Coping Behavioural Parameters in Maturing Rats: Transgenerational effects - Ratti, Silvia Gabriela (2019)
A previous study of our laboratory have shown that Tellurium (Te), a metalloid with low concentrations in soil and water in the earth, is able to modify important behavioural parameters related to cognitive functions when administered orally in maturing rats. Exposition of chronic non-toxic doses of Te affected spontaneous lateralized exploration, social interaction behaviour, and survival responses in the treated rats. Te effects were blocked by the simultaneous administration of folic acid, a well-known methyl group donor in the cell, suggesting an epigenetic mode of action of Te. Te behavioural effects on the second generation (F1 ) still were found in the next third generation (F2 ). In order to evaluate if these transgenerational behavioural alterations in F2 were depending on DNA methylating mechanisms, as observed in the F1 generation, F1 rats were mated at 90 days of age. Two groups of animals in the F2 offspring were formed; one treated with and the other not treated with folic acid. Results showed that the untreated folic acid F2 maturing rats, conserved the same pattern of behavioural alterations than its parents (F1 ), in spite that they were not exposed to Te. Those F2 animals treated with folic acid, instead recovered the normal behavioural responses in the three tests performed to evaluate coping behaviour. Results suggest that the molecular mechanism of Te is dependent on DNA methylating reactions, which is one of the molecular processes of epigenetic modulation in mammals